Evaluation of gall bladder mucosal changes in patients undergoing laparoscopic cholecystectomy - Singh, Harpreet; Kaul, Roop Kishan; Singh, Naveen Kumar; Gupta, Aviral; Yadav, Vikram Singh (International Surgery Journal, 2019)
Background: Histopathological changes induced by gall stone disease or cholelithiasis are diverse including acute inflammation, chronic inflammation, glandular hyperplasia, granulomatous inflammation, cholesterosis, dysplasia and carcinoma. Hence, this study was planned to assess gallbladder mucosal changes in patients undergoing laparoscopic cholecystectomy (LC) and it’s correlation with number and types of stone. Methods: A total of 50 patients with symptomatic cholelithiasis scheduled to undergo laproscopic cholecystectomy (LC) after written and informed consent from October 2015 to October 2018 at Teerthanker Mahaveer Medical College and Research Centre, Moradabad were followed prospectively. Preoperative biochemical profile and ultrasonography of whole abdomen of all the patients was obtained. LC was done under the hands of the skilled and experienced surgeons. Morphologic profile of gallstones was recorded and analysed. Gallbladder mucosal tissues were sent to general pathology department for analysis. Histopathological typing of all the gallbladder mucosal specimens was done and was correlated with the number and type of gallstones. Results: In majority (76%) cases, cholecystitis was found. Hyperplasia was seen in 10% patients. Cholecystitis with metaplasia in 10 percent of the cases and carcinoma in 2 percent of the cases. While correlating the gallbladder mucosal response with the number and type of stones, non-significant results were obtained. Conclusions: There might be some association between gall bladder mucosal changes and gall stone. We cannot say an etiologic and effective correlation from the results of this study; possible mechanism may be gall stone erodes gall bladder wall constantly over a period of time which may constitute a risk. While correlating gallbladder mucosal response with the number and type of stones, non-significant results were obtained.